2022
DOI: 10.9734/ajahr/2022/v9i130132
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Attack of Microbiological Control Agents against Plant Pathogens for Sustainable Agriculture and Food Security

Abstract: Plant diseases accounts for huge losses in agriculture. To ensure food security and sustainability, an agricultural yield must be improved to meet the growing world population. Due to growing awareness of the effect of pesticides and herbicides on human health and the environment, an alternative safe method of controlling phytopathogens has become a subject of intense research. Biological control of plant diseases is the use of living organisms to suppress or inhibit plant pathogens. Microbiological control ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 71 publications
(110 reference statements)
0
4
0
Order By: Relevance
“…Recent years have been marked by an expanding array of virulent infectious diseases caused by pests which are increasingly recognized as presenting a worldwide threat to food security ( Olsen et al, 2011 ; Bosso et al, 2015 ; Hartmann, 2022 ). In addition, the extensive use of agrochemicals molecules has led to the development of bacterial resistance, causing significant risks to the environment and human health ( Ebele Mbachu et al, 2022 ). Consequently, providing food for the world’s population without disrupting the environmental balance is becoming eminent ( Pandit et al, 2022 ).…”
Section: Predatory Actinomycetota As An Eco-friend...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent years have been marked by an expanding array of virulent infectious diseases caused by pests which are increasingly recognized as presenting a worldwide threat to food security ( Olsen et al, 2011 ; Bosso et al, 2015 ; Hartmann, 2022 ). In addition, the extensive use of agrochemicals molecules has led to the development of bacterial resistance, causing significant risks to the environment and human health ( Ebele Mbachu et al, 2022 ). Consequently, providing food for the world’s population without disrupting the environmental balance is becoming eminent ( Pandit et al, 2022 ).…”
Section: Predatory Actinomycetota As An Eco-friend...mentioning
confidence: 99%
“…Different microorganisms are used as biocontrol agents, such as bacteria, fungi, and Actinomycetota ( Table 3 ). Direct antagonism and predation are the possible modes of action of biocontrol agents to eliminate plant parasites ( Ebele Mbachu et al, 2022 ).…”
Section: Predatory Actinomycetota As An Eco-friend...mentioning
confidence: 99%
“…Alternative methods for controlling plant pathogens have gained attention in recent years. These methods rely on the use of antagonistic microorganisms that interact with the pathogen and compete for resources through hyperparasitism ( Mbachu et al, 2022 ). Among these biocontrol agents, Bacillus subtilis BD170 ( Broggini et al, 2005 ), Pseudomonas fluorescens EPS62e ( Pujol et al, 2005 ), P. fluorescens A506 ( Wilson and Lindow, 1993 ), and Pantoea agglomerans E325 ( Pusey et al, 2011 ) have been demonstrated to suppress the fire blight pathogen.…”
mentioning
confidence: 99%
“…These biological agents have been isolated from the ecological niche of plants, cultivated under classical methods, and assessed for their antagonistic activity using in vitro and in vivo analyses ( Köhl et al, 2019 ). As the occurrence of plant diseases is influenced by micro-ecological interactions, analyzing the indigenous microbiome of the host can provide insights into potential sources of natural antagonistic strains that reduce the severity of the pathogen and the genetic mechanisms underlying their beneficial functions ( Köhl et al, 2019 ; Mbachu et al, 2022 ). Ultimately, this can provide a better understanding of the genetic variability of biocontrol agents and another direct mode of action used in biocontrol through ecological microbiome analysis ( Köhl et al, 2019 ).…”
mentioning
confidence: 99%